1952
DOI: 10.1128/jb.63.1.39-45.1952
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibition of Tubercle Bacilli by Analogues of Biotin

Abstract: Woods' report in 1940 on the mode of action of sulfanilamide initiated a new era in the study of chemotherapeutic agents. In the past decade hundreds of new drugs patterned after specific metabolites have been synthesized. Among these are a number of biotin analogues whose inhibitory activity for a variety of organisms has been described. In most instances activity of the compound has been limited to nonpathogenic organsms requiring an exogenous source of the vitamin, but biotin analogues have shown little act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1955
1955
1977
1977

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Having shown that incubation under increased C02 tension substitutes for a requirement for biotin, it seemed of interest to investigate whether increased C02 tension actually eliminates the need for biotin as a necessary growth factor or only decreases the amount of biotin required for C02 assimilation. For this study the biotin analogue 4-(imidazolidone-2) caproic acid" was used because it is known to inhibit growth of tubercle bacilli by antagonizing endogenous biotin (Pope, 1952). The effect of increased C02 tension and of biotin on this inhibition was studied.…”
Section: Tablementioning
confidence: 99%
“…Having shown that incubation under increased C02 tension substitutes for a requirement for biotin, it seemed of interest to investigate whether increased C02 tension actually eliminates the need for biotin as a necessary growth factor or only decreases the amount of biotin required for C02 assimilation. For this study the biotin analogue 4-(imidazolidone-2) caproic acid" was used because it is known to inhibit growth of tubercle bacilli by antagonizing endogenous biotin (Pope, 1952). The effect of increased C02 tension and of biotin on this inhibition was studied.…”
Section: Tablementioning
confidence: 99%